Keanekaragaman Tumbuhan Bahan Kebugaran Dalam Naskah Lontar Rukmini Tatwa Masyarakat Bali - Suryadarma, I.G.P. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Rukmini Tatwa is a traditional health and beauty Balinese script. That script was written on the leaves of palm tree (Borrassus flabellifer). The basic concepts of healthy and beauty are generally considered the integrated result of physical, mental and emotional. Rukmini Tatwa is traditional beauty that refers the practice of using natural plants substances. The script documented more than one hundred plant use, composition and therapy. The plants are prepared in various ways. Parts of plant used are the leaves, flowers, root, stem, bark, fruit, seed and tuber. Most of the concoction is made simply by grinding and pounding. Its knowledge is equal to the traditional medicine. Rukmini Tatwa illustrated to maintain the family harmony from lack of fitness and beauty as well as to solve sexual problems.